HUBUNGAN DUKUNGAN SUAMI DALAM MENGHADAPI KECEMASAN TERHADAP KECEMASAN PERUBAHAN FISIK PADA PRIMIGRAVIDA DI WILAYAH KERJA PUSKESMAS BAYAN KABUPATEN PURWOREJO - Fitriana, Ayu; Kurniawati, Nindya (Jurnal Komunikasi Kesehatan, 2022)
The third trimester is a condition where the mother experiences very significant changes. This anxiety is different for every pregnant woman, but primigravida mothers experience more anxiety than multigravida mothers. This condition requires the support of the closest people, especially the husband as a main supporter. A preliminary survey study conducted at the Bayan Health Center showed 18 primigravida mothers, 8 of whom experienced anxiety. This study aims to analyze the relationship between husband's support and anxiety about physical changes in primigravida in the work area of the Bayan Health Center. The method used is an analytical survey, with a cross-sectional approach. The population of TM III pregnant women with a sample of 36 respondents, the technique used was accidental sampling, which was carried out at the Bayan Health Center, in March. The instrument used was a questionnaire and a statistical test used Chi Square. The results of the Chi Square test are that there is a relationship between husband's support in dealing with anxiety and physical changes in Primigravida in the Bayan Health Center with the result that the p value (0.001) < (0.05) then Ho is rejected, Ha is accepted. It is hoped that health workers can improve health services for pregnant women, especially providing counseling and ANC examinations.